Perancangan Sistem Informasi Inventory Menggunakan Metode FIFO pada Toko Grosir Ceria - Ghani, Abdul; Veri, Jhon; Mardison (Universitas Putra Indonesia YPTK Padang, 2024)
The cheerful grocery store is a business that offers food, drinks, and other necessities. The problem faced by grocery stores is that no system manages business activities and there is also no system for processing inaccurate inventory, receipt, and output data every month. Based on this, this research aims to design an information system by adopting the First in First Out (FIFO) method of performance. The design of this information system is intended to make it easier for cheerful grocery stores to manage business activities. The information system was designed and built using the PHP and MySQL programming languages. It is hoped that the system's work activities will be able to produce better sales, stock, and customer reports. Based on the tests that have been carried out, the resulting inventory information system is capable of controlling the stock of goods so that it can provide information on the existing stock of goods quickly and accurately. Overall, this research can contribute actively to helping the cheerful grocery store in the management of business process activities, especially in the inventory section.